Integrating ethics into the public administration curriculum: a three-step process - Walton, John R.; Crespy, Charles T.; Steams, James M. (1997)
This article provides a three-step process for analyzing public policy dilemmas with ethical implications. A framework is proposed that builds on existing ethics theories and attempts to provide a relevant, usable approach for decision-making. A review of current thought in ethics indicates a concern for two areas: (a) responsibilities to relevant constituencies; and (b) adherence to moral obligations. The framework presented herein directly addresses both of these areas of concern. The authors have found this approach to be useful for classroom applications. This process is simple to explain, understand, and apply to a range of administrative situations. Students find the framework a memorable tool, useful in structuring deliberations with ethical implications. Sample applications of the framework provide examples for educators interested in integrating ethics into their advanced undergraduate and graduate courses. - Reproduced
Keywords: Ethics; Public administration